2017
DOI: 10.1055/s-0043-116948
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Morphine-Induced Tolerance and Dependence by Pretreatment with Cerebrolysin in Male rats

Abstract: In conclusion, it was found that pretreatment with Cerebrolysin could attenuated morphine-induced tolerance and dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
5
0
2
Order By: Relevance
“…Perhaps this relates to one study that demonstrated improvement in morphine tolerance and reduced withdrawal symptoms with Cerebrolysin therapy in an animal study. 6 I still reserve some skepticism, mostly from the origination of Cerebrolysin, but the treatments in the few human studies I have reviewed appeared to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps this relates to one study that demonstrated improvement in morphine tolerance and reduced withdrawal symptoms with Cerebrolysin therapy in an animal study. 6 I still reserve some skepticism, mostly from the origination of Cerebrolysin, but the treatments in the few human studies I have reviewed appeared to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…5 Despite preclinical and clinical data supporting the antinociceptive and potential antimigraine roles of cannabinoids, most headache clinicians have heeded the suggestion to wait for additional data. 6 Here Kandasamy and colleagues provide some additional preclinical data with rats on wheels, as reviewed by WMC. I find most interesting the potential "therapeutic window" effect where some THC was helpful, but too much THC was detrimental.…”
Section: -Wade M Cooper Domentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids are efficient painkillers medicines which used in treatment of severe pain [1]. However, psychological and physical dependence are restricting their use in clinical practice [2]. Finding new approaches to decrease physical and psychological dependence following opioids consumption while retaining their analgesic effects has been pursued in many studies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Лекарственный препарат (ЛП) Церебролизин, изготавливаемый на основе пептидного экстракта мозга молодых свиней, проявляет нейротрофический и нейропротективный эффекты, важные для восстановления пациентов после ишемического инсульта (ИИ) и терапии деменции [1]. Экспериментальные исследования указали на нейротрофический [2], нейропротективный [3], ноотропный [4,5], противоболевой и противовоспалительный [6], антиконвульсантный [7] и противоопухолевый [8] эффекты ЛП Церебролизин. Клинические исследования показали эффективность и безопасность использования ЛП Церебролизин для терапии острого ИИ [9], после черепно-мозговых травм (ЧМТ) и субарахноидальных кровоизлияний [10], при когнитивных нарушениях [11] и расстройствах аутистического спектра [12], а также подтвердили противовоспалительный и антиоксидантный эффекты [13].…”
unclassified